Mathematical modelling of a thin layer drying of apricots in a solar energized rotary dryer - Akpinar, EK; Sarsilmaz, C; Yildiz, C (Wiley, 2004)
In this paper we present a mathematical modelling of a thin layer forced solar drying of apricots. An indirect forced convection solar dryer consisting of a solar heater and a rotary column cylindrical drying (RCCD) cabinet was used in the experiments. Air heated by the solar air heater was forced through the apricots by an electrical fan. Moreover, the natural sun drying experiments were conducted for the comparison at the same time. Fourteen different thin layer mathematical drying models were compared according to their coefficients of determination (r, chi(2), RMSE) to estimate solar drying curves. The effects of the drying air temperature, velocity and the rotation speed of column on the drying model constants and coefficients were predicted by multiple regressions using a linear type model. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: solar drying; solar dryer; thin layer drying models; forced drying; energy